Prevalence and co-infection of schistosomiasis/hepatitis B among rural populations in endemic areas in Hubei, China. (12th November 2019) - Zhang, Yupeng; Xie, Yaofei; Chen, Qi; Chen, Xuyu; Dong, Zhuangzhuang; Tan, Xiaodong
Abstract: Background: Both hepatitis B virus (HBV) infection and schistosomiasis are important public health problems in China. Concurrent infection between HBV and schistosomiasis is often observed in areas where schistosomiasis is endemic. The aim of this study was to determine the prevalence of schistosomiasis and HBV in schistosomiasis-affected areas, to explore whether schistosomiasis patients are more susceptible to HBV and to determine if the prevalence of HBV in high-endemic areas of schistosomiasis is higher than in low-endemic areas. Methods: A total of 6526 participants from 13 villages in Hubei province were included in a cross-sectional study and blood samples were collected and examined. Qualitative variables were compared between groups using Pearson's chi-squared test or Fisher's exact test as appropriate. Results: Of the 6526 participants, the overall prevalence was 8.27% for schistosomiasis and 2.67% for HBV. The prevalence of hepatitis B among participants who were Schistosoma antibody positive (25.37%) was higher than the prevalence in participants who were Schistosoma antibody negative (0.62%; χ 2 =1169.358, p<0.001, odds ratio 54.659). We also observed that there was no difference in the prevalence of hepatitis B between males and females in areas where schistosomiasis was endemic (χ 2 =1.827, p=0.177), but the prevalence of hepatitis B in middle-aged people was higher than in other age groups (χ 2 =47.877, p<0.001). Conclusions: There was an association between schistosomiasis and HBV infection. However, more work is needed to find the causal relationship between schistosomiasis and HBV infection.